Vitamin D supplementation and selected metabolic parameters in patients with type 2 diabetes and obesity: a prospective observational study - Hoffmann, Karolina; Bryl, Wiesław; Bhongade, Bhoomendra; Avagimyan, Ashot; El-Tanani, Mohammed; Rabbani, Syed Arman; Talath, Sirajunisa; Rangraze, Imran Rashid; Wali, Adil Farooq; Ibraheem, Walaa; Satyam, Shakta Mani; Ispas, Sorina; et al. (Frontiers in Endocrinology, 2026)
IntroductionVitamin D deficiency has been implicated in metabolic dysregulation, including insulin resistance and inflammation, commonly observed in patients with type 2 diabetes mellitus (T2DM) and obesity. Evidence on the metabolic impact of vitamin D supplementation in this population remains inconsistent.ObjectiveTo evaluate the effects of high-dose vitamin D3 supplementation on anthropometric and selected metabolic parameters in ambulatory obese patients with T2DM treated with metformin monotherapy.MethodsThis 12-week prospective cohort study included 200 patients with T2DM, allocated to a supplementation group (n = 100; vitamin D3 - 4,000 IU/day) or a control group (n = 100; no supplementation). Primary outcome was change in serum 25-hydroxyvitamin D [25(OH)D] concentration. Secondary outcomes included fasting serum glucose (FSG), glycated hemoglobin (HbA1c), blood pressure (BP), serum calcium, and body mass index (BMI). Predictors of failure to achieve target HbA1c ≤ 6.5% were identified using logistic regression.ResultsAfter 12 weeks, serum 25(OH)D significantly increased in the supplementation group compared with controls (Δ +23.7 vs +1.3 ng/mL; p < 0.001). FSG and HbA1c decreased significantly in the intervention group (Δ –0.4 mmol/L, p = 0.02; Δ –0.6%, p = 0.01, respectively), while no significant changes were observed in systolic or diastolic BP, serum calcium, or BMI. Logistic regression identified higher baseline FSG (OR 1.34, 95% CI 1.12–1.61), longer diabetes duration (OR 1.28, 95% CI 1.07–1.54), and higher BMI (OR 1.21, 95% CI 1.01–1.47) as independent predictors of suboptimal glycemic response.ConclusionsHigh-dose vitamin D3 supplementation significantly improved vitamin D status and was associated with modest improvements in glycemic control in obese patients with T2DM, without affecting blood pressure, calcium, or body weight. These findings support vitamin D repletion as a potential adjunctive strategy in diabetes management, while not allowing causal inference, and warrant further confirmation in randomized controlled trials with longer follow-up.